Efektivitas Ekstrak Daun Cempedak (Artocarpus champeden) Pada Penurunan Kadar Kolesterol Total Tikus Wistar (Rattus novergicus L) Obesitas Yang Diinduksi Diet Aterogenik Modifikasi - Paramita Viantry; Djangan Sargowo; Muhtar Khudori; Fida Rasidah (JPP JURNAL KESEHATAN POLTEKKES PALEMBANG, 2025)
Background: Total cholesterol is an abnormality of blood lipoproteins that can lead to hyperlipidemia and atherosclerosis. Cempedak leaf extract (Artocarpus champeden) contains secondary metabolites such as flavonoids, saponins, steroids, and tannins, which have antioxidant, anti-inflammatory, and anti-hyperlipidemic effects. Methods: Experimental research, pre-post test control group design. The research sample was 25 male white rats of the Wistar strain, 2 months old and with an average body weight of 110 grams. Then divided into 5 groups, namely a positive control modified atherogenic diet, a negative control base, treatment 1 modified atherogenic diet + Cempedak Leaf Extract 120mg/KgBW, treatment 2 modified atherogenic diet + Cempedak Leaf Extract 360mg/KgBW, and treatment 3 modified atherogenic diet + Cempedak Leaf Extract 480mg/KgBW for 14 days. Results: Based on the statistical data analysis of the Paired Sample T-Test, the results were obtained at P1 (p=0.006), P2 (p=0.000), and P3 (p=0.000) where p<0.05 indicated that there was a significant effect (decrease) in total cholesterol levels before and after being given Cempedak Leaf Extract (Artocarpus champeden). Conclusion: Administration of Cempedak Leaf Extract (Artocarpus champeden) has an effect on reducing total cholesterol levels in obese male white Wistar rats induced by an atherogenic diet.